Implementation of Hadith in Contemporary Islamic Law: A Case Study of The Determination of Fatwa Law in The Exchange of New Money Ahead of Eid in Indonesia - Ayu Karina; Endad Musaddad (Riviera Publishing, 2025)
This research aims to examine the implementation of hadith in contemporary Islamic law through a case study of fatwa regarding the exchange of new money ahead of Eid in Indonesia. The method used in this study is a qualitative approach based on case studies using a functional structural approach to understand the social function of the practice. The results of the study show that the practice of money exchange is allowed if there is a separation of contracts between transactions and service fees.